Parental Involvement in Early Childhood Classrooms and Its Influence on Kindergarten Teachers’ Teaching Strategies - Logro, Mara (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of parental involvement on the teaching strategies employed by kindergarten teachers at Busay Elementary School, Cataingan, Masbate. Anchored on Bronfenbrenner’s Ecological Systems Theory, the study explored how parental engagement affects instructional practices and strengthens continuity between home and school learning environments. A qualitative case study design was employed, involving five kindergarten teachers selected through the census method. Data were collected using a validated interview guide with open-ended questions and were analyzed through thematic organization and interpretation. Findings revealed that teachers utilized contextualized and home-based learning activities that linked classroom instruction with children’s everyday experiences. Communication and collaboration with parents were facilitated through communication notebooks, social media platforms, phone calls, meetings, and instructional guides. Teachers also reported challenges such as limited parental availability, low confidence or literacy levels, inadequate access to technology, minimal engagement, and unfavorable home conditions. To support parental involvement, teachers used learning kits, printed guides, instructional videos, storybooks, activity calendars, and visual aids. Parents generally responded positively to these initiatives, demonstrating increased engagement, confidence, and support for their children’s learning. The study concludes that parental involvement significantly influences kindergarten teachers’ instructional strategies by promoting more responsive, inclusive, and home-linked learning experiences. It recommends strengthening home-school partnerships through consistent communication, accessible learning resources, and parent support initiatives that encourage active participation in children’s education. The study aligns with SDG 4 (Quality Education) and SDG 17 (Partnerships for the Goals) by promoting effective learning practices and collaboration among schools, families, and communities. Its sustainability contribution lies in strengthening educational, community, and institutional sustainability through meaningful parent–teacher partnerships that support continuous learner development and educational quality.